Who Suffers the Penalty? A Panel Data Analysis of Earnings Gaps in Vietnam - Christophe J. Nordman; Huu Chi Nguyen; François Roubaud (ZBW - Deutsche Zentralbibliothek für Wirtschaftswissenschaften, Leibniz-Informationszentrum Wirtschaft, 2011)
In spite of its predominant economic weight in developing countries, little is known about informal sector income dynamics vis-à-vis the formal sector. Some works have been done in this field using household surveys, but they only consider some emerging Latin American countries and a few African countries. As a matter of consequence, there is still no way to generalize the (diverging) results to other part of the developing world. Taking advantage of the rich VHLSS dataset in Vietnam, in particular its three waves panel data (2002, 2004, 2006), we assess the magnitude of various formal/informal earnings gaps while addressing heterogeneity issues at three different levels: the worker, the job (wage employment vs. selfemployment) and the earnings distribution.We estimate fixed effects and quantile regressions to control for unobserved individual characteristics. Our results suggest that the informal sector earnings gap highly depends on the workers' job status and on their relative position in the earnings distribution. Penalties may in some cases turn into premiums. By comparing our results with studies in other developing countries, we draw conclusions highlighting the Vietnam's labour market specificity.
Keywords: J21; J23; J24; J31; O17; 330; informal employment; earnings gap; transition matrix; quantile regressions; panel data; Vietnam